Mineralogy and geochemistry of Kliripan manganese ore deposit, Hargorejo Village, Kokap District, Kulonprogo Regency - Islamadina, B. (2022)
This study discusses the mineralogy and geochemistry of manganese deposits in the Kliripan area, where manganese had been mined since the Dutch occupancy until the 1970s. Although mining has been discontinued since then, the demand for manganese has increased in various industries, prompting exploration to continue to meet this demand. We performed petrographic, XRD, and XRF analysis of the ore and wall rock samples. Jasper and grainstone from the Sentolo Formation are the two lithologies where manganese mineralization occurs. Manganese-bearing minerals include pyrolusite, manganite, rhodochrosite, and lithiophorite, while the gangue minerals consist of quartz, calcite, hematite, and clay minerals. We interpret that Jasper is a product of alteration and has MnO content as high as 5.02 wt.. Meanwhile, the economic grade manganese ore in grainstone has an MnO content up to 48.51 wt.. The elements Ce, Zr, Co+Ni+Cu, are important discriminants to determine the type of manganese deposit. The results showed that the diagenetic process in reductive water formed the manganese ores. Oxidation of divalent manganese ion formed pyrolusite and manganite. Rhodochrosite crystallized when dilute manganese solution reacts with CO2 from limestone diagenesis. We concluded that the Kliripan manganese ore deposit has both hydrothermal and diagenetic deposits. © Published under licence by IOP Publishing Ltd.